2009
DOI: 10.1093/neuonc/nop021
|View full text |Cite
|
Sign up to set email alerts
|

Neurolymphomatosis: diagnosis, management, and outcomes in patients treated with rituximab

Abstract: The term "neurolymphomatosis" (NL) has included infiltration of the peripheral nervous system by lymphoma and nontumor lymphocytes. We describe NL as a lymphoma entity that affects cranial and peripheral nerves and roots. We reviewed the medical records of patients at the Massachusetts General Hospital (MGH) who registered between 1972 and 2000, as well as cases published in the English-language literature. Inclusion criteria were (A) histopathologic demonstration of lymphoma within peripheral nerve, nerve roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
94
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(97 citation statements)
references
References 66 publications
2
94
0
1
Order By: Relevance
“…Although the total number of reported NL cases diagnosed by FDG-PET/CT is still small, positive findings are highly suggestive of a diagnosis of NL, particularly in patients with a known history of hematologic malignancy [1,6]. Furthermore, FDG-PET/CT can often diagnose NL when other diagnostic modalities have failed [7], and can allow disease extent to be visualized and therapeutic response to be determined [8].…”
Section: Case Reportmentioning
confidence: 99%
“…Although the total number of reported NL cases diagnosed by FDG-PET/CT is still small, positive findings are highly suggestive of a diagnosis of NL, particularly in patients with a known history of hematologic malignancy [1,6]. Furthermore, FDG-PET/CT can often diagnose NL when other diagnostic modalities have failed [7], and can allow disease extent to be visualized and therapeutic response to be determined [8].…”
Section: Case Reportmentioning
confidence: 99%
“…Peripheral nervous system (PNS) involvement is usually secondary to spread from systemic and only rarely it is primary as seen in our patient [2]. The relative incidence of NL is estimated to be about 3% of newly diagnosed NHL cases [3]. NL usually presents in four ways: 1) painful polyneuropathy or polyradiculopathy (most common; usually lumbosacral or cauda equina roots, rarely cervical or thoracic; usually subacute to chronic, rarely acute like Guillain-Barre syndrome), 2) cranial neuropathy (20%; most common facial nerve followed by abducens, oculomotor and trigeminal nerve involvement), 3) painless neuropathy (sensory before motor) and 4) peripheral mononeuropathy (usually sciatic, rarely median, radial or intercostal nerve involvement).…”
Section: Discussionmentioning
confidence: 66%
“…The clinical course is either progressive or relapsing remitting. Whatsoever the initial site, NL ultimately diffusely infiltrates peripheral neural structures as well as CSF and the substance of brain and spinal cord [3].…”
Section: Discussionmentioning
confidence: 99%
“…Neurolymphomatosis occurs in 8.5-29% of non-Hodgkin's lymphoma cases [1]. Although some cases have been reported to have recurrence with neurolymphomatosis after the complete remission of a diffuse large B-cell lymphoma (DLBCL) with treatment [2], no case of neurolymphomatosis exhibiting repeated exacerbation and spontaneous remission in the central (CNS) as well as peripheral nervous systems (PNS) has been reported. Here, we report the first case of neurolymphomatosis that exhibited repeated exacerbation and spontaneous remission in both the PNS and CNS over the long term.…”
Section: Dear Editormentioning
confidence: 99%
“…It was reported that neurolymphomatosis may develop after a complete remission of primary lesion of lymphoma with treatment of rituximab [2]. While, large B-cell neurolymphomatosis may be confined to the PNS without CNS lesions throughout clinical course [5].…”
Section: Dear Editormentioning
confidence: 99%